Elementos definitorios del Periodismo Digital - Caminos Marcet, José María; Marín Murillo, Flora; Armentia Vizuete, JOSÉ IGNACIO (Estudios sobre el Mensaje Periodístico, 2007)
The cyberjournalism in Spain in the last ten years has been analyzed by several authors so much from a theoretical point of view as from more pragmatic other one. These analyses have established a series of basic characteristics of what today we understand as journalism online. We have gathered in this text the the essential characteristics of this new journalistic modality departing from a series of authors who are specially important for the study of the cyberjournalism. This article is a part of a research financed by the University of the Basque Country called “Ten years of dailys online in Spain”